Identification, Molecular Characteristics, and Evolution of GRF Gene Family in Foxtail Millet (Setaria italica L.) - Chen, Huilong; Ge, Weina (Frontiers in Genetics, 2022)
Growth-regulating factor (GRF) is a multigene family that plays a vital role in the growth and development of plants. In the past, the GRF family of many plants has been studied. However, there is not a report about identification and evolution of GRF in foxtail millet (Setaria italia). Here, we identified 10 GRF genes in foxtail millet. Seven (70.00%) were regulated by Sit-miR396, and there were 19 optimal codons in GRFs of foxtail millet. Additionally, we found that WGD or segmental duplication have affected GRFs in foxtail millet between 15.07 and 45.97 million years ago. Regarding the GRF gene family of land plants, we identified a total of 157 GRF genes in 15 representative land plants. We found that GRF gene family originated from Group E, and the GRF gene family in monocots was gradually shrinking. Also, more loss resulted from the small number of GRF genes in lower plants. Exploring the evolution of GRF and functional analysis in the foxtail millet help us to understand GRF better and make a further study about the mechanism of GRF. These results provide a basis for the genetic improvement of foxtail millet and indicate an improvement of the yield.